2016
DOI: 10.1637/11458-062216-reg
|View full text |Cite
|
Sign up to set email alerts
|

Marek's Disease in Backyard Chickens, A Study of Pathologic Findings and Viral Loads in Tumorous and Nontumorous Birds

Abstract: Marek's disease (MD) is a major cause of mortality in backyard chickens. The diagnosis of MD is complex, however, and knowledge of Marek's disease virus (MDV) in spontaneous field cases such as in backyard chickens is largely unknown. In this study, 40 backyard chickens with a presumptive MD diagnosis based on histologic lymphoid infiltrations in peripheral nerves with and without lymphomas were investigated. Twenty-eight of the birds were submitted to the diagnostic laboratory for disease explorations, and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…As reports of the MDV strain in Brazil are scarce, even more in backyard chicken flocks, this study remembers the importance of the vigilance. On the other hand, the apparition of MDV in backyard flocks is a common event [51] with the presence of low and high-virulence pathotypes [52,53]. The pathogenicity of the MDV strain detected in this study could be comparable with the highest virulent ones, based on the percentage of mortality (>10%) and the lymphoproliferative lesions observed in necropsy (Figure 1a,b) and histopathologic examination (Figure 2a-d).…”
Section: Discussionmentioning
confidence: 51%
“…As reports of the MDV strain in Brazil are scarce, even more in backyard chicken flocks, this study remembers the importance of the vigilance. On the other hand, the apparition of MDV in backyard flocks is a common event [51] with the presence of low and high-virulence pathotypes [52,53]. The pathogenicity of the MDV strain detected in this study could be comparable with the highest virulent ones, based on the percentage of mortality (>10%) and the lymphoproliferative lesions observed in necropsy (Figure 1a,b) and histopathologic examination (Figure 2a-d).…”
Section: Discussionmentioning
confidence: 51%
“…Affected birds remain infectious for life continuously shedding the virus into the environment contaminating the poultry house environment. MD has been reported in all poultry-rearing countries (Dunn & Gimeno, 2013;Mete et al, 2016) and a 2004 estimate suggested that MD causes annual losses of up to US$2 billion to the poultry industry (Morrow & Fehler, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Coinfection with 2–3 viruses has become an important epidemiologic situation in poultry production. 2,9,14,15,17 Many reports have described and compared histologic changes associated with single virus infection; 1,7,8 however, histologic findings and antigen distribution from naturally occurring cases of coinfection have been reported only rarely.…”
mentioning
confidence: 99%